Modulators of Transient Receptor Potential (TRP) Channels as Therapeutic Options in Lung Disease - Alexander Dietrich (MDPI AG, 2019)
The lungs are essential for gas exchange and serve as the gateways of our body to the external environment. They are easily accessible for drugs from both sides, the airways and the vasculature. Recent literature provides evidence for a role of Transient Receptor Potential (TRP) channels as chemosensors and essential members of signal transduction cascades in stress-induced cellular responses. This review will focus on TRP channels (TRPA1, TRPC6, TRPV1, and TRPV4), predominantly expressed in non-neuronal lung tissues and their involvement in pathways associated with diseases like asthma, cystic fibrosis, chronic obstructive pulmonary disease (COPD), lung fibrosis, and edema formation. Recently identified specific modulators of these channels and their potential as new therapeutic options as well as strategies for a causal treatment based on the mechanistic understanding of molecular events will also be evaluated.